New Insights on the Seismic Activity of Ostuni (Apulia Region, Southern Italy) Offshore - Pierpaolo Pierri; Marilena Filippucci; Vincenzo Del Gaudio; Andrea Tallarico; Nicola Venisti; Vincenzo Festa (Applied Sciences)
On 23 March 2018, an event of magnitude ML 3.9 occurred about 10 km from the town of Ostuni, in the Adriatic offshore. It was the most energetic earthquake in South–Central Apulia ever recorded instrumentally. On 13 February 2019, in the same area, a second ML 3.3 event was recorded. The analysis of the 2018 event shows that the ambiguity of the solution of the fault plane reported by INGV (Istituto Nazionale di Geofisica e Vulcanologia) on the Italian National Earthquake Centre website can be solved considering existing seismic profiles, exploration well logs and the Quaternary activity of faults in the epicentral area. A seismogenic source was identified in the rupture of a small portion of a 40 km length structure with strike NW-SE, dipping at a high angle toward the south. In this work, we have relocated the recent earthquakes by using the seismic stations managed by the University of Bari (UniBa), one of which is quite close to the event’s epicenter (about 20 km), together with data coming from the RSN (Rete Sismica Nazionale). Furthermore, we have determined the focal mechanism of some events, with implications on stress field of the area. Our results show right-lateral transtensional kinematics of the seismogenic faults along approximately E-W striking planes, with a tension, T, with a trend of about 60° (NE-SW direction) and a plunge of 20°. Finally, we have tried to correlate the location of the four best constrained earthquakes with their seismogenic structures.